Anesthetic Management of a Pediatric Patient with Popliteal Pterygium Syndrome Undergoing Labiopalatoplasty: A Case Report - Peter Leonardo; Novita Anggraeni; Vera Muharrami (HM Publisher, 2025)
Background: Popliteal pterygium syndrome (PPS) is a rare congenital disorder characterized by multiple anomalies, including orofacial, musculoskeletal, and genitourinary defects. Airway management in PPS patients can be challenging due to associated craniofacial abnormalities. This case report describes the anesthetic management of a 5-month-old infant with PPS undergoing labiopalatoplasty. Case presentation: A 5-month-old male infant, weighing 5.9 kg, presented for labiopalatoplasty. He had a diagnosis of PPS with associated labiopalatoschisis, ankyloblepharon filiforme, pterygium in the popliteal fossa, cryptorchidism, and syndactyly. Airway assessment revealed a patent airway with a cleft lip and palate. Anesthesia was induced with sevoflurane and maintained with sevoflurane and nitrous oxide. Direct laryngoscopy was unsuccessful, and videolaryngoscopy was used to facilitate tracheal intubation. Conclusion: This case highlights the challenges of airway management in infants with PPS. A thorough preoperative airway assessment and the availability of alternative intubation techniques, such as videolaryngoscopy, are crucial for successful anesthetic management in these patients.